Development of a speech controlled water tap and fan system using linear predictive coefficient for feature extraction - S. Okomba, Nnamdi; O. Esan, Adebimpe; Omodunbi, Bolaji; A. Adeyanju, Ibrahim; A. Bashir, Sulaimon (International Journal of Engineering and Technology, 2019)
Automatic device control is of great assistance in different electronic application areas that will aid human endeavors. Traditionally, fan and water pump system used in many homes are controlled by using manual process. This is a time consuming and difficult procedure, for the elderly, and handicap persons. In this view, this paper presents a microcontroller based fan and water pump control system using speech recognition. The system has a PIC16F628A microcontroller activated by a speech recognizer, then triggers control to a DC motor which set the water tap or the fan in motion. The Spoken words chosen for recognition are ON and OFF and the speech samples were extracted with Linear Predictive Coefficient (LPC) Feature extraction technique and after experimenting with the developed system, the result indicates the device is of good performance. We intend to increase the complexity of this work by adding specific sensors that will automatically switch off the fan at specified room temperature, and turn off the water tap at the fill of a container. Â Â